Application of oleaster leaves (Elaeagnus angustifolia L.) essential oil and natural nanoparticle preservatives in frankfurter-type sausages: An assessment of quality attributes and stability during refrigerated storage. (April 2023) - Yaghoubi, Milad; Alirezalu, Kazem; Hesari, Javad; Peighambardoust, Seyed Hadi; Marcinkowska-Lesiak, Monika; Barzegar, Younes; Hoseinian-Khosrowshahi, Seyed Razi; Marszałek, Krystian; Mousavi Khaneghah, Amin
Abstract: The effects of oleaster leave essential oil (OLEOs: 1000 and 2000 ppm) in combination with nisin nanoparticles (200 ppm) and ε-polylysine nanoparticles (2000 ppm) on the physicochemical, microbiological and sensory properties of the emulsion-type sausages without added chemical nitrite/nitrate salts were evaluated during 45 days of storage. Nanoparticle attributes were assessed, including encapsulation efficiency (EE%), zeta potential, nanoparticles size, FTIR analysis, and thermal stability (DSC). Overall, ε-PL nanoparticles (ε-PL-NPs) were thermally more stable and showed higher EE% (91.52%) and zeta potential (37.80%) as compared to nisin nanoparticles (82.85%) and (33.60%), respectively. The use of combined ε-PL-NPs (2000 ppm) + Ni-NPs (200 ppm) with oleaster leaves essential oil (2000 ppm) resulted in a higher pH value (5.88), total phenolic content (10.45 mg/100 g) and lower TBARS (2.11 mg/kg), and also decreased total viable bacteria (1.28 Log CFU/g), Clostridium perfringens (1.43 Log CFU/g), E. coli (0.24 Log CFU/g), Staphylococcus aureus (0.63 Log CFU/g), and molds and yeasts (0.86 Log CFU/g) count in samples at day 45 in comparison to the control (120 ppm nitrite). The consumers approved sensory traits in nitrite-free formulated sausages containing ε-PL-NPs and Ni-NPs combined with OLEOs. Highlights: Stability and quality properties of emulsion-type sausages containing ε-PL-NPs, NI-NPS in combination with OLEOs were evaluated. Combined natural antimicrobials improved the pH, TBARS in the sausages. Combinations of OLEOs and nanoparticles reduced Clostridium perfringens, E. coli and Staphylococcus aureus in sausages. Sausages combined with ε-PL-NPs, NI-NPS, and OLEOs had a good sensory acceptance.